HABITATS USED BY WILD TURKEY HENS DURING THE SUMMER IN OAK FORESTS IN PENNSYLVANIA - Anthony S. Ross; Gerald A. Wunz (Wildlife Society Bulletin)
Abstract: We studied the habitats used by 33 radio‐marked eastern wild turkey (Meleagris gallopavo silvestris) hens during 7 summer seasons in the mixed oak (Quercus spp.) forests of the Ridge and Valley physiographic Province of southcentral Pennsylvania where conventional brood habitat of herbaceous vegetation is scarce. Normally, this area supported low‐density turkey populations. The summer season was divided into early (May through 15 Jul) and late (16 Jul through Sep) brood‐rearing periods. Turkey hens successfully raised broods in forests where natural clearings were rare. During early summer, most broods used lowland habitats where herbaceous plant stands existed in the forests. By late summer, most broods shifted to upland sites to feed on fruits of blueberry (Vaccinium spp.) and huckleberry (Gaylussacia spp.). Hens without broods were typically found in upland habitats throughout the summer (P < 0.001). Most radio locations of hens were in forest stands where conifers were an important component. Encouraging some conifer stands in oak forests with dense shrub understories could have practical management implications.